Transcriptome RNA-seq revealed lncRNAs activated by Edwardsiella anguillarum post the immunization of OmpA protecting European eel (Anguilla anguilla) from being infected. Issue 118 (November 2021) - He, Wenxuan; Wu, Liqun; Li, Senlin; Guo, Songlin
Abstract: Long noncoding RNAs (lncRNAs) play important roles in various biological activities as vital regulators. However, no study has focused on the lncRNA regulation of Outer membrane protein (OMP) immunization against aquatic bacterial infection. In this study, we examined the genome-wide expression of lncRNAs in the liver of European eel ( Anguilla anguilla, Aa ) administrated by a recombinant OmpA (rOmpA) from Edwardsiella anguillarum ( Ea ) to elucidate the functions of lncRNAs in the process of Ea infection and Aa anti- Ea infection using strand specific RNA-seq. Eels were challenged by Ea at 28 d post the immunization (dpi) of OmpA, and the result showed, compared to uninfected livers in the PBS group (Con group), the infected livers in the PBS group (Con_inf group) showed severe bleeding, hepatocyte atrophy and thrombi formed in the hepatic vessels; livers in the OmpA group (OmpA_inf) also formed slight thrombi in the hepatic vessels. The relative percent survival of eels in OmpA_inf vs Con_inf was 78.6%. Using high-throughput transcriptomics, we found 13405 lncRNAs in 3 compares of Con_inf vs Con, OmpA_inf vs Con and OmpA_inf vs Con_inf, of which 111, 129 and 158 DE-lncRNAs were ascertained. GO analysis of the DE-lncRNAs revealed the targeting DEGs were mainly involved in single-organism process, signaling, biological process and response to stimulus in BP, component of membrane in CC and binding in MF; KEGG pathways showed that the targeting DEGs in co-expression and co-location enriched in cell adhesion molecules. Finally, 54 DE-lncRNAs targeting 1675 DEGs were involved in an interaction network of 21692 co-expression and 483 co-location related links, of which 18 DE-lncRNAs appear to play crucial roles in anti- Ea infection. Thus, the interaction networks revealed crucial DE-lncRNAs underlying the process of Ea infection and Aa anti- Ea infection pre and post the immunization of OmpA. Highlights: LncRNAs activated by the infection of E. anguillarum after immunization was first reported. The pathological changes of liver were greatly relieved after the OmpA immunization. The relative percent survival of European eels was 78.6% after the OmpA immunization. Eighteen DE-lncRNAs appear to play crucial roles in anti- E. anguillarum infection.